Perbandingan Pengaturan Hukum Terkait Skema Ponzi : Perspektif Indonesia dan Amerika Serikat dalam Perlindungan Investor - Rendy Claudio Krisna Iroth; Nadhira Zahra Farida; Ilham Daffi Syabana (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
In Indonesia, the use of technology to make investments is getting easier as time goes by. However, it is unfortunate that some companies and individuals use this technology to run illegal businesses without a license from the Financial Services Authority. One form of illegal business that is on the rise is the Ponzi scheme system. A Ponzi scheme is a form of financial fraud in which the perpetrator offers a high rate of return/profit to investors, which is paid using newly incoming funds from subsequent investors. This research uses normative juridical research method, which is a legal research method conducted with the aim of finding legal principles and theories associated with existing practices in the field. This research is conducted by comparing the legal approach between the regulations in Indonesia and the United States related to Ponzi Schemes. Considering that in Indonesia the legal arrangements regarding Ponzi Schemes are generalized which makes Indonesia have no legal certainty for the protection of investors, through comparison with one of the countries with developed economies, namely the United States. This aims to provide a better understanding of the different legal approaches and efforts that can be made to overcome the Ponzi Scheme problem and can provide education to the public who may have a layman's understanding of Ponzi scheme investments.